A Pragma-Semantic Analysis Of Jordanian Proverbs And The Factors Behind Their Misinterpretation - Dawaghreh, Abdullah Mahmoud Mustafa (2021)
Proverbs are replete with a rhetorical force and polymorphous nature which may result in misinterpretation of proverbs or the main essence of a proverb not being fully captured. Technically, such linguistic lacunae and drawbacks jeopardize the chances of conveying the intended message appropriately. This can give rise to a state of imbalance in the scale of communication and understanding. The language user, therefore, needs a pragmatic competence to be able to interpret proverbs properly. The purpose of this study is to examine the subtle implications and cryptic meanings of Jordanian proverbs from a pragmatic and semantic perspective. An attempt is made by the researcher to show the main linguistic factors that might give rise to difficulty in understanding Jordanian proverbs. Data was collected orally. The researcher collected 322 proverbs from the subjects of this study. Eighty proverbs have been randomly chosen. The data was studied and analyzed in terms of pragmatic and semantic views. In other words, for the purpose of achieving the objectives of this study, the researcher has adopted the linguistic approach that relies on basic semantic and pragmatic concepts cogently advocated by mainstream scholars of semantics and pragmatics such as Lawal et al. (1997), Grice (1975) and Searle (1976). Obviously, the approach proves effective and fruitful in figuring out the cryptic meaning that resides in Jordanian proverbs, let alone the fact that such a method of analysis proves effective in showing the factors that impede the language user from grasping the intended meaning of proverbs.